Quantile Regression Estimates for Hydro Balance and Temperature Affecting Electricity Spot Price - Kyllönen, Markus (My University, 2012)
Electricity has become an exchange-traded commodity in many parts of the world as local electricity networks have been connected into larger, international power pools for price stability and security in power delivery at all times. The Nordic power market Nord Pool is considered a forerunner in creation of the continental European power market. In practice the process has been challenging as Nord Pool still has several price areas caused by physical transmission restrictions. Also the prices have not been stable as the physical nature of the non-storable electricity sets strict requirements for supply to meet the circumstance-driven demand. The current market structure has created new financial risks for operators in the field of electricity, and understanding the factors behind electricity prices has become increasingly important. It is known that the demand i.e. electricity consumption is highly dependent on the seasonal temperature circumstances, creating changes in the need for heating and cooling. The production as supply leans on the availability of generation and therefore on costs of utilized fuels. The environmental circumstances in the Nordic region are rather challenging with cold winters and hydropower representing half of the power generation. Especially when cold seasons occur simultaneously with the low hydro fuel balance, the market balance is endangered and the risk for extreme price reactions has increased. The thesis estimates the explanatory effect of Oulu temperature and Scandinavian hydro balance on Nord Pool Finnish area price, within the variable value range using quantile regression. The effect was expected to reach its highest at the negative extremes of variables and decrease towards the normal and up. In the Nordic region, hydro balance reflects the long-run price levels, while mean reversion and extreme price jumps are affected by short-term fluctuation in temperature.
Keywords: Nord Pool; electricity spot price; temperature; hydro balance; quantile regression.; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|